2015
DOI: 10.4103/0976-9668.149069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acute respiratory infection among under-five children in urban and rural areas of puducherry, India

Abstract: Introduction:The incidence of Acute respiratory infections (ARI) is high among under-five children, especially in developing countries. However, the data on ARI from rural and urban areas in India are scarce.Objective:To estimate the prevalence of ARI and selected associated factors among under-five children.Materials and Methods:A community-based cross-sectional study was conducted in urban and rural areas of Puducherry, India. Data were collected from 509 parents of under-five children regarding ARI incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 7 publications
10
56
4
2
Order By: Relevance
“…Male patients seem to have greater susceptibility to ARI as compared to female patients which is also seen in our study and in studies conducted by Vinod et al, Goel, Kumar and Chhabra et al 7,9,11,12 On the contrary, Acharya et al in her study revealed similar prevelance of ARI among both the sexes. 13 According to Mother's education of ARI Children, 53.48% of ARI cases was observed in illiterate mothers but no association in respect to ARI and literacy status of mother was found (p≥0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Male patients seem to have greater susceptibility to ARI as compared to female patients which is also seen in our study and in studies conducted by Vinod et al, Goel, Kumar and Chhabra et al 7,9,11,12 On the contrary, Acharya et al in her study revealed similar prevelance of ARI among both the sexes. 13 According to Mother's education of ARI Children, 53.48% of ARI cases was observed in illiterate mothers but no association in respect to ARI and literacy status of mother was found (p≥0.05).…”
Section: Discussionsupporting
confidence: 88%
“…In a study carried out by Kumar et al, 52.7% had cold/running nose, 45.4% had cough, 3.3% of had sore throat, 1.2% had ear discharge, 2% had symptoms associated with fever and fast breathing, 47.5% had symptoms associated with fever. 16 In a study done by Fekadu et al, 20.6% had cough, 15.7% had fast breathing, 7.7% had fever, 8.4% had wheezing, 2.1% had chest in drawing and 1.7% had stridor. 24 In a study carried out by Majumdar et al, 85.7% had cough, 100% had runny nose, 1.8% had ear discharge and none had sore throat.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Kumar SG et al, the prevalence of acute respiratory infection among under-five children in urban and rural areas of Puducherry, was found to be 53.7% in rural area. 16 In another study conducted by Choube et al, Potential risk factors contributing to acute respiratory infections in under five age group children in Moradabad, the prevalence was 27.69%. 20 In a study done by Kapil et al, on prevalence of acute respiratory infections (ARI) in under-five children of Meerut district, it was 67.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, son consideradas uno de los principales eventos en salud pública, por el alto porcentaje de consultas y hospitalizaciones que genera en los menores de 5 años, así como las altas cifras de morbilidad y mortalidad que produce a nivel mundial. En países subdesarrollados estas infecciones junto con las enfermedades diarreicas agudas y la malnutrición representan las principales causas de muerte en niños [1][2][3] .…”
Section: Introductionunclassified